A Prospective Phase II Study of Pegaspargase-COEP Plus Radiotherapy in Patients With Newly Diagnosed Extra-Nodal NK/T-Cell Lymphoma - Hu, Shaoxuan; Lin, Ningjing; Liu, Jiaxin; Sun, Yan; Liu, Weiping; Wang, Xiaopei; Xie, Yan; Song, Yuqin; Wen, Yi; Zhu, Jun (Frontiers in Oncology, 2022)
Background: The optimal first-line treatment for extra-nodal NK/T-cell lymphoma (ENKTL) has not been well-defined. This study aimed to evaluate the efficacy and safety of pegaspargase, cyclophosphamide, vincristine, etoposide and prednisone (COEPL) regimen combined with radiotherapy for patients with newly diagnosed ENKTL. Methods: Our study is a prospective, open-label clinical trial. Patients with newly diagnosed ENKTL and an ECOG performance status of 0 to 2 were eligible for enrollment. For patients with stage I/II nasal ENKTL, treatment included 2 cycles of induction COEPL regimen followed by concurrent chemoradiotherapy, then by 2 cycles of COEPL regimen as consolidation. For patients with stage III/IV or primary extra-nasal ENKTL, treatment included 6-8 cycles of COEPL regimen with or without radiotherapy to local sites, and autologous stem cell transplantation was given in selected patients. Results: A total of 80 patients were enrolled. The median age was 41 years (range, 15-76 years). Sixteen patients (20%) had stage III/IV disease, and 10 (12.5%) had a PINK score≥2. Complete response and overall response rates were 75.9% and 87.3%, respectively. With a median follow-up of 41.4 months (range 2.7-76.2 months), the 3-year progression-free survival (PFS) and overall survival (OS) rates were 71.3% (95%CI 61.1-81.5%) and 73.3% (95%CI63.1-83.5%), respectively. For patients with stage I/II nasal ENKTL (n=62), the 3-year PFS and OS were 78.1% and 81.2%, respectively. For patients with stage III/IV or primary extra-nasal ENKTL (n=18), 3-year PFS and OS were 48.1% and 45.7%, respectively. Major grade 3-4 adverse events were anemia (21.3%), leucopenia (22.5%), neutropenia (18.8%), and thrombocytopenia (7.6%). No treatment-related death was observed. Conclusions: Pegaspargase-COEP chemotherapy in combination with radiotherapy is highly effective and safe for patients with newly diagnosed ENKTL.